Educação em saúde na prevenção do risco de desmame precoce Health education in the prevention of premature weaning - Nelly Martins Ferreira Candeias (Universidade de São Paulo, 1983)
Procurou-se determinar, a partir de um conjunto de cinco variáveis, idade, paridade, intervalo intergestacional, renda "per capita" mensal da família e escolaridade, quais delas produzem maior poder discriminatório quanto ao tempo médio do aleitamento natural e, para estas, qual a estratificação ótima. A análise estatística, de acordo com o método de Morgan e Sonquist, permitiu conhecer as características de mulheres com maior risco de desmame precoce. Propõe-se a utilização dos conceitos de "risco de desmame precoce" e "risco infantil acumulado". A study was made to verify which of five variables, age, parity, spacing of pregnancies, family income per month "per capita" and schooling had the greatest effect on the average length of the period of breast-feeding and, for each variable, which was the critical point. Statistical analysis according to Morgan and Sonquist statistical method permitted the recognition of the characteristic of women with greatest risk of premature weaning. The use of the concepts "premature-weaning risk" and "accumulated child risk" was proposed.